AN UPDATED CHECKLIST OF THE MOSQUITOES FROM SOUTH SUMATRA PROVINCE WITH A NEW RECORD OF AEDES (DOWNSIOMYIA) PEXUS COLLESS, 1958 (DIPTERA: CULICIDAE) IN INDONESIA - Sidiq Setyo Nugroho; Mujiyono Mujiyono; Triwibowo Ambar Garjito; Riyani Setiyaningsih; Siti Alfiah; Yahya Yahya; Anif Budiyanto; Lasbudi Pertama Ambarita (BRIN Publishing (Penerbit BRIN), 2017)
Data of mosquito fauna is important to be known as basic effort in vector mosquito control. It is necessary to update the data from time to time. The effort of updating the mosquito fauna was started from South Sumatra Province. Amount of 2,784 mosquito specimens were examined. The result showed there are 62 species of mosquitoes from South Sumatra Province and they belong to 10 genera. One species of culicid mosquito were recorded for the first time from Indonesia, namely Aedes (Downsiomyia) pexus and six other species were first recorded on Sumatra Island. These species are now included in the Sumatran Culicidae checklist.